Deep Seated Lobular Capillary Hemangioma (Pyogenic Granuloma) of the Colon: A Rare Case Requiring Surgery beyond Endoscopic Management. (29th March 2022) - Park, Jaechun; Jung, Minjung
Abstract : Background . Lobular capillary hemangiomas typically present as skin or oral mucosa lesions and have rarely been described in unusual sites, including the gastrointestinal tract. Most colonic lobular capillary hemangiomas, either asymptomatic or associated with GI bleeding, have been amenable to endoscopic treatment in literatures. Case Presentation . A 41-year-old woman presented with an incidental colonic mass during a systemic workup after adjuvant chemotherapy for HER2-positive breast cancer. Abdominal computed tomography revealed a deep seated colonic mass in the splenic flexure. An endoscopic strip biopsy was attempted for differential diagnosis of this lesion, but uncontrolled bleeding occurred, and an emergency surgery was eventually performed. Microscopic examination showed lobular capillary hemangioma involving full thickness of the colonic wall with mucosal ulceration. Conclusions . Colonic lobular capillary hemangioma is a benign vascular proliferation but is a candidate in differential diagnosis of benign or malignant tumors. Furthermore, the exceptional case may be deep seated and require more invasive surgery, unlike most cases of colonic lobular capillary hemangioma that can be treated with endoscopic modality.